Strategi Humas dalam Membangun Brand Image Pasca Covid-19 di Taman Pintar Yogyakarta - Alvin Joachim Junior Asy; Yulinda Erlistyarini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Taman Pintar Yogyakarta, an educational park in the city of Yogyakarta, experienced a decline in visitors of up to 230 thousand during the pandemic. To increase the number of visitors, it is necessary to improve the brand image of Taman Pintar. Public relations strategy is the main step in this effort, especially by utilizing social media such as Instagram. This research aims to analyze the strategies used by Taman Pintar in improving its brand image after Covid-19. This research method is qualitative with data collection through interviews, observation and documentation. The PR strategy theory used is from Rosady Ruslan, which includes creating positive activities to build a good image, creating public opinion and getting feedback, establishing positive relationships with the community, and creating harmonious relationships between the organization and the audience. The results of the research show that the Taman Pintar Public Relations team carries out activities that involve the community, maintains good relations with partners, holds internal activities to increase harmony, always evaluates activities and criticism received, and uses social media to build a positive image. The results of this research show that Taman Pintar Smart itself has its own strategy for improving its brand image, namely by utilizing social media as a branding medium.